Subsidized childcare and child development in Colombia: Effects of Hogares Comunitarios de Bienestar as a function of timing and length of exposure - Bernal, Raquel; Fernández, Camila (Social science & medicine (1982), 2013)
Rigorous evidence regarding the impact of early care and education on children's development comes primarily from high-income nations. A few studies from Latin America and the Caribbean have identified benefits of conditional cash transfer and home visiting programs on children's development. However, there is still controversy around the impact and cost-effectiveness of childcare approaches. Further research is needed to understand how scaled-up childcare settings may support the development of low-income children in Latin America. To that end, the present study sought to identify the effects of exposure to a subsidized childcare program in Colombia on children's nutritional status, cognitive and socioemotional development. This community-based program, known as Hogares Comunitarios de Bienestar (HCB), serves 800 thousand low-income children under age 6, delivering home-based childcare, supplementary nutrition, and psychosocial stimulation. We analyzed data on 10,173 program beneficiary children (ages 3–6) collected in 2007. We compared beneficiary children who had been in the program for a long time with beneficiary children who had been in the program for a month or less, by age group, to estimate program exposure effects. We used a matching estimator to correct for self-selection into different exposure levels. Results indicated that cognitive development improved 0.15 to 0.3 of a standard deviation (SD) after at least 15 months of exposure for children between 3 and 6 years of age. Socioemotional skills improved 0.12 to 0.3 SD for children older than 3 after at least 15 months of program exposure. No significant gains were found for nutritional status. The estimated benefit-cost ratio ranged from 1.0 to 2.7, depending upon varying discount rates. Findings lend support for a potentially effective strategy to promote the development of low-income children in Colombia and other developing nations. ► We estimated effects of length of exposure to the largest public childcare program in Colombia on children's development. ► We found modest effects of the program on children's cognitive and socioemotional development but not on nutritional status. ► Scores on cognitive development were up to 0.3 SD higher for older children exposed to the HCB program 15 months or longer. ► Older children exposed to the HCB program for at least 15 months exhibited less withdrawal and isolation behaviors. ► The estimated benefit-cost ratio suggests that the HCB program may potentially afford beneficiaries a modest increase future earnings.